2019
DOI: 10.1155/2019/6297162
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data in Support of Short Sleep Duration with Poor Glycemic Control, in People with Type 2 Diabetes Mellitus

Abstract: Aims. Sleep duration (SD) has been associated with metabolic outcomes. Is there an independent association between short/long SD and glycemic control (GC) in type 2 diabetes mellitus (T2DM) outpatients, compared to intermediate SD? Employing up-to-date definitions of SD, we comprehensively considered, simultaneously, all known confounding/mediating factors that recently emerged in the literature: age, gender, diet, physical activity, obesity, night pain, nocturnal diuresis, sleep quality, chronotype, sleep apn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…28 These factors may contribute to the impaired glycaemic control observed in evening chronotypes. [9][10][11][12] Moreover, increased levels of fatigue experienced by evening chronotypes 10,16 could exacerbate feelings of failure and reduce resilience, leading to a negative emotional impact on how they manage their diabetes. 6,7 Therefore, recognising the different chronotype categories and their association with diabetes-related distress could help people with diabetes and professionals formulate diabetes management plans that are better tailored to the needs of the individual and their chronotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 These factors may contribute to the impaired glycaemic control observed in evening chronotypes. [9][10][11][12] Moreover, increased levels of fatigue experienced by evening chronotypes 10,16 could exacerbate feelings of failure and reduce resilience, leading to a negative emotional impact on how they manage their diabetes. 6,7 Therefore, recognising the different chronotype categories and their association with diabetes-related distress could help people with diabetes and professionals formulate diabetes management plans that are better tailored to the needs of the individual and their chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that both lack of sleep and excessive amounts of sleep increase the risk of developing type 2 diabetes and worsen glycaemic control in established type 2 diabetes. [9][10][11][12] Chronotype is largely genetically determined and describes an individuals' inherent pattern for their sleep-wake cycle scheduling and aligns with when they are most alert; early risers and late sleepers define the two extremes of chronotype. 8,9 Chronotype can be determined using the Morningness-Eveningness questionnaire (MEQ) in which a high score relates to morningness tendencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor-sleep habits were further reflected in the calculated PSQI score with an average score for the general population of 6.8 (SD± 3.2). Short sleep duration was shown previously to significantly increase the risk of developing type 2 diabetes (4, 24), cardiometabolic risks (25), dyslipidemia (26) and other metabolic syndromes (MetS). Although it is still unclear how sleep duration might drive MetS, it seems that sleep deprivation is becoming a worldwide problem.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this inflammation is due to hyperglycemia 3 . Another significant part of this inflammation is secondary to sleep disorders (sleep deprivation, insomnia, sleep-related breathing disorders, and circadian rhythm sleep-wake disorders) very prevalent in these patients 4 . In addition to a greater circulation of inflammatory agents, both DM2 and sleep disorders determine a lower amount of an important anti-inflammatory agent: melatonin [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%